Evaluation of Neck Disability Using Computed-Tomography in Head and Neck Cancer Survivors - Harris, Alexandria; Branstetter, Barton; Li, Jinhong; Piva, Sara R.; Johnson, Jonas T.; Nilsen, Marci Lee (Frontiers in Pain Research, 2022)
Objective We have previously reported that 55% of head and neck cancer survivors have neck disability. However, it is unclear what factors contribute to their neck disability. Our study aim is to determine if survivors with neck disability have evidence of cervical spine degenerative disease assessed by computed tomography (CT). Materials/Methods Cross-sectional analysis of patient-reported neck disability, prospectively collected on survivors of squamous cell carcinomas without recurrence or metastasis over one-year post-treatment. Neck disability and its impact on daily life was measured using the Neck Disability Index (NDI) and compared with cervical CT scans within 6 months. Scans were evaluated for degeneration of the disc and facet of the cervical vertebrae rated on a 5-point scale where 5 indicates more severe disease. Multivariable linear regression was used to analyze the association between NDI and radiographic findings. Results 116 survivors of oropharyngeal carcinomas were identified, predominantly male (81.9%) with an average age of 62.8 ± 8.2 (range 43.8–81.4). Most survivors had advanced stage III-IVa cancer (94.0%) with treatment modalities including surgery (n=26, 52.0%), chemotherapy (n = 45, 90.0%), and radiation therapy (n = 49, 98.0%). Absence of neck disability was observed in 44.0% of survivors, 39.7% had mild disability, and 16.4% moderate disability. The time from treatment to clinic visit was an average of 3.1 ± 2.7 years (range 1.1–13.4). Multivariable analysis of NDI controlling for age, time since treatment, and treatment modality identified an inverse association between NDI and spinal degenerative disease examining cervical discs (−1.46 95% confidence interval (CI) [−2.86, −0.06], p = 0.041) and age (−0.24 95% CI[−0.40, −0.08], p = 0.004). Conclusions Our study shows that neck impairment and pain in head and neck cancer survivors is not sufficiently explained by cervical degeneration related to age or trauma, supporting the theory that post-treatment neck disability occurs as a side effect of treatment. These results support the further assessment of structure and function of cervical musculature and degeneration following HNC treatment.